2014
DOI: 10.1590/abd1806-4841.20142399
|View full text |Cite
|
Sign up to set email alerts
|

Keratosis pilaris and prevalence of acne vulgaris: a cross-sectional study

Abstract: BACKGROUNDAcne vulgaris has an important genetic predisposition, as well as keratosis pilaris. Clinical observations suggest that patients with keratosis pilaris have less frequent or less severe acne breakouts; however, we found no studies on this regardOBJECTIVETo determine if the presence of keratosis pilaris is associated with lower prevalence and severity of acne.METHODSA cross-sectional study was conducted with dermatology outpatients aged between 14 and 35 years. We evaluated history and clinical grade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 13 publications
2
2
0
Order By: Relevance
“…We observed KP in 82% of patients, an overall higher frequency than the 11–73% range observed in genetic studies of CFCS, but close to that of a large paediatric dermatological study . Mild‐to‐moderate KP is not unusual in children and adolescents in the general population (2–26%), those with CS (9–33%) and those with SOS1 ‐mutated NS (up to 50%) . However, generalized KP involvement, present in about one‐quarter of our cases of CFCS, is usually not mentioned in large series of patients with CS or NS and therefore could provide a valuable clinical orientation sign for CFCS.…”
Section: Discussionsupporting
confidence: 80%
“…We observed KP in 82% of patients, an overall higher frequency than the 11–73% range observed in genetic studies of CFCS, but close to that of a large paediatric dermatological study . Mild‐to‐moderate KP is not unusual in children and adolescents in the general population (2–26%), those with CS (9–33%) and those with SOS1 ‐mutated NS (up to 50%) . However, generalized KP involvement, present in about one‐quarter of our cases of CFCS, is usually not mentioned in large series of patients with CS or NS and therefore could provide a valuable clinical orientation sign for CFCS.…”
Section: Discussionsupporting
confidence: 80%
“…Considering their relatively lower frequencies and the potentially significant changes in scalp hair characteristics during childhood and adolescence in NS, these hair abnormalities appear to be of little use for diagnosing NS. We observed KP in 18·5% of patients, which is a relatively higher frequency than 6% as previously reported, but not significant given that KP frequencies in children and adolescents in the general population vary from 2% to 26% …”
Section: Discussionsupporting
confidence: 47%
“…More than half of our patients gave a history of only mild comedonal acne, none requiring systemic medications. Schmitt et al reported a lower severity of acne vulgaris in patients with KP pilaris of the arms. The lower acne severity in patients with KP may be due to a lower sebaceous secretion or to a differentiated follicular keratinization determined by genetic factors such as those observed in the chromosome 18p deletion syndrome …”
Section: Discussionmentioning
confidence: 97%
“…KP severity was subjectively graded by the same investigator as absent, mild, moderate, and severe (0 to 3), according to the density and intensity of follicular keratotic papules and of the associated erythema and hyperpigmentation . Dermoscopic examination of the affected areas was also done to confirm diagnosis and to determine the severity …”
Section: Patientsmentioning
confidence: 99%